Discordant CSF/plasma HIV-1 RNA in individuals on virologically suppressive antiretroviral therapy in Western India. Issue 8 (February 2018) - Dravid, Ameet N.; Natrajan, Kartik; Kulkarni, Milind M.; Saraf, Chinmay K.; Mahajan, Uma S.; Kore, Sachin D.; Rathod, Niranjan M.; Mahajan, Umakant S.; Wadia, Rustom S.
Abstract : Abstract: Aim of this study was to estimate the prevalence of cerebrospinal fluid (CSF)/Plasma HIV-1 RNA discordance in virologically suppressed individuals presenting with incident neurologic symptoms. In this retrospective cohort study conducted between March 1, 2009, and March 1, 2017, HIV-1 infected adults exposed to atleast 12 months of antiretroviral therapy (ART) and having plasma viral load (VL) <1000 copies/mL (virologically suppressed) were included. Among these, individuals presenting with neurologic symptoms during follow-up were assessed for CSF/Plasma HIV-1 RNA discordance by measuring HIV-1 RNA in collected plasma and CSF samples. CSF/plasma HIV-1 RNA discordance was defined as either detectable CSF HIV-1 RNA (VL > 20 copies/mL) with an undetectable plasma RNA (complete viral suppression, VL ⩽20 copies/mL) or CSF HIV-1 RNA ≥ 0.5 log10 higher than plasma RNA when plasma VL was between 20 and 1000 copies/mL (low-level viremia, LLV). Out of 1584 virologically suppressed patients, 71 (4.4%) presented with incident neurologic symptoms. Twenty out of 71 (28.2%) patients were diagnosed with CSF/Plasma HIV-1 discordance. Median plasma and CSF VL in patients with discordance was 120 [interquartile range (IQR): <20 to 332.5] and 4250 (IQR: 2550.0– 9615.0) copies/mL, respectively. All 9 individuals in which CSF HIV-1 genotypic resistance testing was done showed mutations that would compromise efficacy of prescribed ART regimen. Prevalence of CSF/plasma HIV-1 RNA discordance was higher among neurologically symptomatic patients with plasma LLV as compared with those with complete viral suppression (70% vs 11.8%, P < .001). The risk of discordance was also greater in patients who received protease inhibitor (PI) containing ART ( P < .001) and those on ART regimens with central nervous system (CNS) penetration effectiveness (CPE) value <6 ( P = .006). CSF/plasma HIV-1 RNA discordance indicates replication of HIV-1 that has adapted to the CNS or has developed antiretroviral drug resistance. Larger studies should be performed to study incidence of discordance in India. This will help in managing patients presenting with neurologic symptoms on suppressive ART with appropriate neuroeffective therapy.